2016
DOI: 10.1016/j.jaa.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Gravettian firewood procurement near the Pavlov Hills, Czech Republic

Abstract: This paper draws attention to firewood as a natural resource that was gathered, processed and consumed on a daily basis by Palaeolithic groups. Using Gravettian occupation of the Pavlovské Hills as a case study (dated to around 30,000 years B.P.), we investigate firewood availability using archaeological, palaeoenvironmental and ecological data, including making inferences from charcoal in Pavlovian hearths. The collated evidence suggests that while dead wood was likely readily available in woodland areas wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…The charcoal data also add to a growing corpus of macrofossil evidence that indicates the survival of trees in mammoth steppe environments on the Central Russian Plain throughout the last glacial cycle (Tzedakis et al 2013). The availability of deadwood fuel supplies is a prerequisite for many modern hunter-gatherers in high-latitude cold climates (Pryor et al 2016). The presence of conifer trees near Kostenki-perhaps located in low-lying, moist and sheltered areas in the ravines near to the site-would have been an important resource that attracted hunter-gatherers to the area during the glacial period.…”
Section: Discussionmentioning
confidence: 84%
“…The charcoal data also add to a growing corpus of macrofossil evidence that indicates the survival of trees in mammoth steppe environments on the Central Russian Plain throughout the last glacial cycle (Tzedakis et al 2013). The availability of deadwood fuel supplies is a prerequisite for many modern hunter-gatherers in high-latitude cold climates (Pryor et al 2016). The presence of conifer trees near Kostenki-perhaps located in low-lying, moist and sheltered areas in the ravines near to the site-would have been an important resource that attracted hunter-gatherers to the area during the glacial period.…”
Section: Discussionmentioning
confidence: 84%
“…This quickly depleted local fuel sources and indicated that fuel and food scarcity, not water availability, led to increasing mobility among these foragers. Due to local environmental features, Gravettian hunter-gatherers in the Pavlov Hills region of the Czech Republic likely quickly eliminated the naturally-occurring deadwood, and it may have taken several generations (40-120 years) for the deadwood to regenerate (Pryor et al, 2016). The authors proposed that these Gravettian people used intentional management strategies, such as geographic mobility and the deliberate killing of trees in advance, in order to provide enough fuel for their planned visits to the sites.…”
Section: There Are Many Potential Costs To Fire Many Of Which Can Bementioning
confidence: 99%
“…While previous work has considered some of the costs associated with fire, including both time (Dunbar and Gowlett, 2014) and resources (Kaufman and Scott, 2014;Pryor et al, 2016), the actual energetic costs of creating a fire have never been quantified. These must be measured in order to have a meaningful comparison to the benefits of fire.…”
Section: Advantages Of Employing An Economic Approachmentioning
confidence: 99%
“…Examining the remains and function of Palaeolithic hearths is therefore a key research issue that may contribute towards identifying some of the past behaviours surrounding early human uses of fire and fuel. More specifically, the identification of materials used for fuel via micro or macro remains from combustion features can provide information archaeologically on local environments, the types of fuel used and fuel management strategies (Carrión et al 2010;Pryor et al 2016;Henry and Théry-Parisot 2014;Théry-Parisot 2001, 2002aVidal-Matutano et al 2017). Identifying materials used for fuel in the archaeological record may also provide information on other important behaviourally relevant functions relating to hearth activity if the combustion properties of a fuel could be determined to provide enough benefit for a particular purpose.…”
Section: Introductionmentioning
confidence: 99%